2018
DOI: 10.1084/jem.20180534
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages of distinct origins contribute to tumor development in the lung

Abstract: Tissue-resident macrophages can self-maintain without contribution of adult hematopoiesis. Herein we show that tissue-resident interstitial macrophages (Res-TAMs) in mouse lungs contribute to the pool of tumor-associated macrophages (TAMs) together with CCR2-dependent recruited macrophages (MoD-TAMs). Res-TAMs largely correlated with tumor cell growth in vivo, while MoD-TAMs accumulation was associated with enhanced tumor spreading. Both cell subsets were depleted after chemotherapy, but MoD-TAMs rapidly recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
210
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(223 citation statements)
references
References 61 publications
12
210
1
Order By: Relevance
“…Tissue-resident interstitial macrophages (CD64 + Siglec F − ) have recently been reported to contribute to the population of tumour-associated macrophages [12]. To exclude the possibility that these tissue-resident peribronchial or perivascular interstitial macrophages can migrate to the alveolar space in response to asbestos-induced epithelial injury and differentiate into alveolar macrophages, we treated Cx3cr1 ER-Cre ×ZsGreen reporter mice with tamoxifen to label tissue-resident interstitial macrophages (figure 2d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-resident interstitial macrophages (CD64 + Siglec F − ) have recently been reported to contribute to the population of tumour-associated macrophages [12]. To exclude the possibility that these tissue-resident peribronchial or perivascular interstitial macrophages can migrate to the alveolar space in response to asbestos-induced epithelial injury and differentiate into alveolar macrophages, we treated Cx3cr1 ER-Cre ×ZsGreen reporter mice with tamoxifen to label tissue-resident interstitial macrophages (figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue-resident alveolar macrophages originate from fetal monocytes, populate the alveolar niche soon after birth, are capable of self-renewal and, in mouse models, persist in the lung without appreciable input from myeloid cells over the lifespan of the animal [7][8][9][10]. Lung tissue-resident interstitial macrophages have been shown to include perivascular and peribronchial macrophages, which demonstrate distinct anatomical localisation and function [11][12][13][14]. In response to alveolar macrophage depletion and/or injury, monocytes are recruited to the lung where factors present in the microenvironment drive their differentiation into alveolar macrophages [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…TAMs can be proliferative, which could provide a compensatory mechanism when monocyte recruitment is impaired . Recent work has demonstrated that in lung metastatic sites, TAMs are derived from both CCR2‐dependent monocytes and resident interstitial Mϕs, each promoting tumor growth and metastatic spreading, respectively . Additional work is needed to better understand the relative contributions of monocytes and resident Mϕ populations to TAM accumulation and phenotype across different tumor types.…”
Section: Functions In Cancermentioning
confidence: 99%
“…The majority of macrophages present in the tumor microenvironment are recruited from bone marrow-derived monocytes through the CC chemokine 2 (CCL2/CCR2) [28][29][30][31] and colony stimulating factor 1 (CSF-1/CSF-1R) [32] signaling pathways. However, studies have identified a mixture of yolk sac-derived and bone marrow-derived macrophages in the tumor microenvironment suggesting that, depending on their origin, TAMs have different roles during tumor progression [33][34][35]. TAMs secrete inflammatory cytokines, growth factors and proteolytic enzymes that promote cell proliferation, invasion, and angiogenesis [7,36,37].…”
Section: Macrophagesmentioning
confidence: 99%